Post Abdominal Hysterectomy Ureterovaginal Fistula - Giri, Kanti Prabha; Dangal, Ganesh; Karki, Aruna; Pradhan, Hema; Shrestha, Ranjana; Bhattachan, Kabin; Thakur, Amarnath; Poudel, Rekha; Bajracharya, Nishma; Tiwari, Kenusha Devi (Nepal Journal of Obstetrics and Gynaecology, 2018)
Ureteric injury can occur during any pelvic or abdominal surgeries. Gynecological surgeries especially total abdominal hysterectomy is one of the common cause of iatrogenic ureteric injury leading to ureterovaginal fistula. A 35 years lady had continuous leaking of urine per vagina from 25th day after total abdominal hysterectomy. Her CT urogram showed left distal ureterovaginal fistula and she underwent left ureteroneocystostomy. A good knowledge of pelvic anatomy is necessary along with a good surgical skill to prevent ureteric injury during surgery. Keywords: DJ stent, ureteric injury, ureterovaginal fistula.